2004
DOI: 10.1103/physrevlett.93.097401
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Spin-Orbit Sum Rule for the Actinide5fStates

Abstract: The branching ratio of core-valence transitions in electron energy-loss spectroscopy and x-ray absorption spectroscopy is linearly related to the expectation value of the spin-orbit operator of the valence states. Here, we analyze the branching ratio of the N(4,5) edges in the actinides and find that the spin-orbit sum rule gives an accurate result without the need to include the core-valence interactions. The branching ratio is not only useful to study the variations in the 5f spin-orbit interaction, it also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
178
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(195 citation statements)
references
References 22 publications
17
178
0
Order By: Relevance
“…The latter result is rather surprising, since in spite of the fact that the Th 4d core level is more shallow than the Zr 2p of Hf 2p and lies in between the Ti 2p and La 3d, the core-valence interactions do not spoil the sum rule for the 5f states. Our calculations showed that B 0 varies between only 0.59 and 0.60 for the light actinides (see Table I) and, therefore, are very close to the statistical ratio [15]. This means that the EELS and XAS branching ratios depend almost solely on the 5f spin-orbit expectation value per hole, and thus we now have an unambiguous probe for the 5f spin-orbit interaction.…”
Section: Of 15supporting
confidence: 64%
See 2 more Smart Citations
“…The latter result is rather surprising, since in spite of the fact that the Th 4d core level is more shallow than the Zr 2p of Hf 2p and lies in between the Ti 2p and La 3d, the core-valence interactions do not spoil the sum rule for the 5f states. Our calculations showed that B 0 varies between only 0.59 and 0.60 for the light actinides (see Table I) and, therefore, are very close to the statistical ratio [15]. This means that the EELS and XAS branching ratios depend almost solely on the 5f spin-orbit expectation value per hole, and thus we now have an unambiguous probe for the 5f spin-orbit interaction.…”
Section: Of 15supporting
confidence: 64%
“…However, for the 5f states of the actinides the spin-orbit interaction is much stronger, giving a significant mixing of the Hund's rule ground state by other LS states with the same J value. Hence, the LS states will be less pure and there is a tendency towards the jj coupling limit [14,15]. The choice of the coupling limit has profound implications for the expectation value of the spin-orbit interaction, as well as for any other orbital-related interactions, such as the orbital magnetic moment.…”
Section: Spin-orbit Interaction and Branching Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Also the M 4,5 edge of the rare earth has large errors, but the edges of the 4d, 5d, and 5f systems have negligible errors due to the mixing of the spin-orbit split components. 8 Crocombette et al 9 also tested the effective spin sum rule theoretically. For an octahedral system at 300 K they found that the sum-rule value for ͗S z ͘ is ϳ10% too small for 3d 6 , 3d 7 , and 3d 8 .…”
Section: ͑⍀͒D⍀ ͑1͒mentioning
confidence: 99%
“…The effective spin sum rule has been theoretically simulated and tested by Teramura et al 7 They calculated the expectation values of the effective spin ͗SE z ͘ and compared them with simulated effective spin sum-rule values ͓SE z sum ͔. van der Laan et al 8 used the ratio of the G 1 ͑pd͒ Slater integral and the core hole spin-orbit coupling to estimate the purity of the L 2 and L 3 edges and as such the accuracy of the effective spin-orbit sum rule. They found the largest error for the L edges of 3d transition metals.…”
Section: ͑⍀͒D⍀ ͑1͒mentioning
confidence: 99%